A review of the genus Trachystolodes Breuning, 1943 (Coleoptera: Cerambycidae: Lamiinae: Lamiini) - Huang, Gui-Qiang; Guo, Liang; Liu, Peng-Yu (Zootaxa, 2020)
A taxonomic review of the genus Trachystolodes Breuning is presented. A new species, Trachystolodes huangjianbini sp. nov., is described from southeast China. Trachystolodes tonkinensis Breuning, 1943 is redescribed and its distribution is discussed. Trachystolodes is redescribed and a key to three known species of Trachystolodes is presented.